Road Accident Prediction Using Machine Learning (International Journal of Scientific Research in Science and Technology, 2024)
Road accidents are a significant cause of fatalities and injuries worldwide. Predicting road accidents is crucial for implementing  preventive  measures  and  saving  lives.  This  paper  presents a deep learning-based road accident prediction  system  utilizing  various  factors  such  as speed, traffic condition, weather, and more. By leveraging publicly available datasets and external data sources, the model aims to accurately predict road accidents, ultimately contributing to enhancing road safety.
Keywords: Road Accidents; Machine Learning; Traffic Prediction; Accident Prevention